2015
DOI: 10.1038/aps.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

The PPARγ agonist, rosiglitazone, attenuates airway inflammation and remodeling via heme oxygenase-1 in murine model of asthma

Abstract: Aim: Rosiglitazone is one of the specific PPARγ agonists showing potential therapeutic effects in asthma. Though PPARγ activation was considered protective in inhibiting airway inflammation and remodeling in asthma, the specific mechanisms are still unclear. This study was aimed to investigate whether heme oxygenase-1 (HO-1) related pathways were involved in rosiglitazone-activated PPARγ signaling in asthma treatment. Methods: Asthma was induced in mice by multiple exposures to ovalbumin (OVA) in 8 weeks. Prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…HO‐1 has been shown to protect against the inflammatory responses induced by various insults including LPS (Liu et al ., ; Xu et al ., ). Therefore, we confirmed these results in an in vivo study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HO‐1 has been shown to protect against the inflammatory responses induced by various insults including LPS (Liu et al ., ; Xu et al ., ). Therefore, we confirmed these results in an in vivo study.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, PPARγ activation by rosiglitazone significantly increases HO‐1 expression and attenuates airway inflammation and remodelling (Xu et al ., ). In this study, blockade of PPARγ by its antagonist (GW9662) or siRNA, diminished rosiglitazone‐mediated PPARγ phosphorylation and promoter activity in HPAEpiCs, suggesting the dependence of PPARγ on HO‐1 expression.…”
Section: Discussionmentioning
confidence: 97%
“…Reduced airway inflammation and mucus production [123,124]. Beneficial effect on lung fibrosis in IPF and in bleomycin-induced lung injury [127,128].…”
Section: Pparγ Agonistsmentioning
confidence: 99%
“…It has been confirmed to play important roles in regulating substrate metabolism, inflammatory responses, cell proliferation, and apoptosis (Balupillai et al, ; Han et al, ; Ivanova, Myasoedova, Melnichenko, & Orekhov, ). Furthermore, activation of PPAR‐γ has been shown to attenuate airway remodeling in a murine model of asthma (J. Xu et al, ) and inhibit the proliferation of human ASMCs in vitro (Ward, Gould, Harris, Bonacci, & Stewart, ), suggesting that PPAR‐γ might be a potential target for the treatment of airway remodeling in asthma. A study by Green, Murphy, Kang, Searles, and Hart () has also demonstrated that activation of PPAR‐γ attenuates hypoxia‐induced proliferation of human pulmonary artery smooth muscle cells (PASMCs) through the downregulation of miR‐21.…”
Section: Introductionmentioning
confidence: 99%